PENERAPAN BLENDED LEARNING DALAM PEMBELAJARAN BIOLOGI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI IPA 4 PUTRA SMA RSBI PONDOK PESANTREN MODERN ISLAM ASSALAAM SUKOHARJO TAHUN PELAJARAN 2011/2012 - Cahyadi, Ferry Dwi; Suciati, Suciati; Probosari, Riezky Maya (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? It already been known that biology as a branch of science will emphasizes on how to think critically to gain most of its basic concepts. Hence, the weaknesses of mastering this kind of skill will be followed by the unsuccessful mastering of its concepts respectively. Factual phenomenon observed towards high school student of the grade of XI of Assalam Islamic Boarding School in academic year 2011/2012 showed that student performing a teacher centered classical learning. Student has never induced and motivated to be a real learner. This, makes student are unable to perform good critical thinking skill. This is real problem in this class that needs to be solved trough particular strategy. Blended learning is expected to be an effective strategy since it facilitates both, student centered learning and optimizing the use of ICT based learning. This research is aimed to ascertain 1) blended learning implementation in biological learning process, 2) blended learning implementation in biological learning process. This research belongs to classroom action research consist of four cycle and each have four phases, namely planning, actuating, observing and reflecting. The subject of the research is XI IPA 4 Putra students at SMA RSBI Pondok Pesantren Modern Islam Assalaam Sukoharjo in academic year 2011/2012. The data was collected by test and non test technique, it was carried out by using essay test, observation sheet, questionnaire, and interview. The obtained data were analyzed using descriptive approach and validated through triangulation method. The results showed that the average percentage of critical thinking aspect from essay test, such as the 1st cycle 56,82%, the 2nd cycle 61,93%, the 3rd cycle 68,94% and the 4th cycle 75,75%. Therefore, it can be concluded that 1) blended learning could be applied in biological learning process, 2) blended learning could be used to improve critical thinking. Keywords: blended learning, critical thinking, biology learning process